2006
DOI: 10.1038/sj.mp.4001926
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of serotonin transporter gene promoter polymorphism (5-HTTLPR) association with selective serotonin reuptake inhibitor efficacy in depressed patients

Abstract: The serotonin transporter gene promoter polymorphism (5-HTTLPR) has been repeatedly associated with antidepressant response in mood disorder patients, but findings are not consistent across studies. A meta-analysis was performed on 15 studies including data of 1435 subjects. We tested three phenotypes: remission rate, response rate and response rate within 4 weeks using the cochrane review manager. We observed a significant association of the s/s variant of 5-HTTLPR with remission rate (P < 0.0001) and both s/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
301
3
10

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(340 citation statements)
references
References 46 publications
26
301
3
10
Order By: Relevance
“…A comprehensive meta-analysis, including over 1400 participants revealed a modest association of the short variant of the 5-HTTLPR with poor response and remission to antidepressants. 15 These findings were subsequently replicated by two large pharmacogenetic studies: Genome-based Therapeutic Drugs for Depression (GEN-DEP) 16 and STAR*D, the latter after considering the ethnicity of the study population. 17 Results from the GENDEP study also suggested that the association is drug specific.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…A comprehensive meta-analysis, including over 1400 participants revealed a modest association of the short variant of the 5-HTTLPR with poor response and remission to antidepressants. 15 These findings were subsequently replicated by two large pharmacogenetic studies: Genome-based Therapeutic Drugs for Depression (GEN-DEP) 16 and STAR*D, the latter after considering the ethnicity of the study population. 17 Results from the GENDEP study also suggested that the association is drug specific.…”
Section: Introductionmentioning
confidence: 86%
“…There is evidence to suggest that 5-HTTLPR genotypes operate in either a recessive or additive genetic model in both the moderation of the effects of stress and response to antidepressants. 15,20 Therefore, interactions based on both genotypic models were tested.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…There are several alleles within 5-HTTLPR, but the most frequent are short (S) and long (L) allele, composed of either 14-or 16-repeat units. The 5-HTTLPR short allele suppresses transcriptional activity of the promoter [14], and it is associated with a poor treatment response to SSRI [32].…”
mentioning
confidence: 99%
“…Platelet 5-HT concentration has been found to be altered in different neuro-psychiatric disorders, personality traits and behaviors [13,22,26,27], and it is significantly decreased after treatment with various SSRI [2,22]. It has been proposed that peripheral 5-HT platelet content can mirror the state of the central 5-HT system [3], and that baseline platelet 5-HT concentration might be used as a predictor of the antidepressant treatment response [5,21,22], while long allele of the 5-HTTLPR is related to a good response to antidepressants [32]. The reports on the association between 5-HTTLPR and platelet 5-HT concentration are inconsistent, showing either positive, negative or no association between 5-HTTLPR genotypes and increased, unaltered or decreased platelet 5-HT concentration [8,9,13,33].…”
mentioning
confidence: 99%
“…This variant, the insertion of a 43 base pair segment in the promoter region (L-allele) together with the A-allele of the SNP rs25531 in the same region seem to affect gene expression in important ways (43), and thus differential expression of the SSRIs’ target became a good hypothesis to explain SSRI efficacy. A meta-analysis of 15 published studies that included 1,520 patients concluded that there was evidence in favor of a significant association of the long (L) allele with better response to SSRIs (44). This result may reflect publication bias because negative studies tend not to get published.…”
Section: Results Of Pharmacogenetics Studies In Star*dmentioning
confidence: 99%